Optimizar parámetros del secado de la pulpa de Genipa americana (huito) por spray dryer microencapsulado con maltodextrina y goma arábiga - Matias Isuiza, Julia Silvia Natalia (2023)
The main objective of this research work is experimental and its main objective was to determine the optimal parameters in drying the pulp of Genipa Americana (huito), using the atomization method applying various encapsulants. The experimental design applied was 3 factors: F1 type of encapsulant (maltodextrin and gum arabic), F2 temperature (°C) and F3 air speed; Therefore, 9x3= 27 experimental treatments were carried out for the two encapsulants, which led to a total of 54 experimental treatments. The concentration percentages (%) used for each encapsulant were: maltodextrin (6%) and gum arabic (6%), respectively. The spray dryer was programmed with the following temperatures: (160°C, 170°C and 180°C); The air speed used was (9.25 mL/min, 16.50 mL/min, 23.75 mL/min), the optimal performance parameters obtained in drying were: maltodextrin (temperature was 170 °C, speed of drying air of 9.25 mL/min, the drying time was 4 h and gum arabic (temperature of 180 °C, drying air speed of 9.25 mL/min, the drying time was 4 h). The results of physicochemical analysis of the pulp of Genipa Americana (huito) microencapsulated with maltodextrin reported a humidity of 6.67%, 1.79% ash, 0.20% fat, 37.66% proteins, 45.30% carbohydrates, 7.66% fiber, 4.4 pH, 14.20° Brix of soluble solids, 93.33% of total solids, 78.04 mg of vitamin C and 337.59 kcal; while, the pulp Genipa Americana (huito) microencapsulated with gum arabic reported a humidity of 6.63%, 1.87% ash, 0.29% fat, 39.55% protein, 48.36% carbohydrates, 7.58% of fiber, 4.4 pH, 14.30 ° Brix of soluble solids, 93.37% of total solids and 77.68 mg of vitamin C and 354.34 kcal. The solubility analysis was 5 min in distilled water and 10 min in liquor (11% alcohol); The sensory analysis reports greater acceptability of the product in powder sprayed with maltodextrin due to its flavor, smell and because it is a fine powder.